How to reach a fair share for the Pestana hotel group in the French and Spanish leisure markets: pricing strategy - Silva, Sofia Miranda Rosa Delgado da (2022)
This paper takes a theoretical approach on how to effectively develop a pricing strategy for a good or service. Furthermore, the work includes a more practical approach in which it is proposed a pricing strategy to PHG, in specific for the Pousadas and the Pestana Collection. Pestana Hotel Group(PHG)is below the fair share of revenues in the Spanish and French markets, in Portugal. Since proximity travels are the ones predicted to recover faster after the COVID-19 pandemic, Pestana aims to seize the opportunity to attract these consumers. Primary and secondary research were conducted to get a better understanding of the ideal Positioning that PHG should adopt in each of the markets, which served as a basis for the proposed Marketing Mix.